(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
In light of the increasing importance of interim financial statements they provided these lists of information that enables users of accounting information to make wise investment decisions and predict the company’s activities in light of changes the updated rather than wait until the end of the year and accessing information provided by the annual financial statements. In light of this research has come to the most important set of conclusions the adoption of interim financial information has been audited by the external auditor to the availability of basic qualitative characteristics in the accounting information contained in the (appropriate and timely manner, reliability and comparability) and this in turn leads to the impact on reliability. As well as presenting a set of recommendations, the most important adoption of the interim financial statements and the program and audit report interim financial information proposed by the external auditors who have audited the annual financial statements for companies because it includes the foundations to be adopted in the preparation of the report review of interim financial information